Cutaneous Tuberculosis: A Diagnosis Too Common, Yet Too Far - Akanksha Mahajan; Taru Garg; Kiran Agarwal; Varinder Singh (Wolters Kluwer Medknow Publications, 2022)
Background: Cutaneous tuberculosis (TB) is a rare disease seen by the pediatrician on an outpatient basis. It has a varied presentation and is classified on the basis of the source of infection and host's immune response to mycobacteria. Lupus vulgaris (LV) is a paucibacillary manifestation of cutaneous TB. It can mimic other infectious skin diseases such as TB verrucosa cutis and chromoblastomycosis. Clinical Description: We hereby present a case report of an adolescent female with a serpiginous, nodular, and warty hyperpigmented skin lesion over her buttock. The lesion had started following incidental injury 7 years back as a papule and continued to expand despite multiple medications. Management: A skin biopsy was done which was suggestive of cutaneous TB, but the absence of systemic features confounded the diagnostic type. She was finally diagnosed as having LV after a detailed review with a dermatologist and pathologist. The patient responded well to antitubercular treatment. Conclusion: Although cutaneous tuberculosis is well described, it is often not recognized by the primary care physician. Diagnostic dilemmas may arise due to clinical-histopathological mismatch.